Front garden, Sam Lord's Castle - (:unkn) unknown (Wilson and Johnstone, Trinidad, 2010)
The postcards shows the front garden at Sam Lord's Castle. Postcard number J413.
Colour: Black and white; Style: Portrait; Other: Unbordered, Divided
Keywords: Barbados; Postcards; Castles--Barbados; Hotels--Barbados; Historic gardens--Barbados; Architecture--Barbados; Plants--Barbados; Outdoor furniture--Barbados; Historic buildings--Barbados